Leaching Characteristics of Udipsamment Ameliored by Mineral Soil and Adhesive Polymer - Fibrianty, Fibrianty; Hanudin, Eko; Ma’as, Azwar (UNIVERSITY OF LAMPUNG, 2022)
UdipsammentÂ isÂ characterizedÂ byÂ sandÂ fractionÂ > 95%,Â loose,Â andÂ veryÂ highÂ leaching. ThisÂ studyÂ aimedÂ to determineÂ theÂ effectÂ ofÂ mineralÂ soilÂ ameliorantsÂ andÂ adhesiveÂ polymersÂ onÂ the characterÂ ofÂ nutrient leachingÂ inÂ Udipsamment.Â TheÂ leachingÂ Â studyÂ inÂ lysimetersÂ usedÂ a completelyÂ randomizedÂ designÂ with threeÂ replications.Â TheÂ treatmentsÂ consistÂ ofÂ bagasseÂ (B),Â mineralÂ soil includedÂ InceptisolÂ (I)Â and VertisolÂ (V),Â and adhesiveÂ polymers included tapiocaÂ 1% and 2% (T1Â andÂ T2),Â tapiocaÂ dregsÂ 1%Â andÂ 2Â %Â (A1 andÂ A2),Â PolyvinylalcoholÂ 0.1%Â andÂ 0.2%Â (P1Â andÂ P2).Â CombinationÂ ofÂ treatmentsÂ areÂ IB,Â VB,Â IBT1, IBT2,Â VBT1,Â VBT2,Â IBA1,Â IBA2, VBA1 ,Â VBA2 , IBP1,Â I BP2, VBP1,Â andÂ VBP2.Â ObservationsÂ were madeÂ beforeÂ andÂ afterÂ leaching.Â TheÂ researchÂ showedÂ thatÂ VBT2Â increases moisture-holdingÂ capacity. Amelioration improved the ability ofÂ UdipsammentÂ toÂ holdÂ nutrients,Â after leachingÂ forÂ sixÂ months,Â there wasÂ aÂ decreaseÂ inÂ organicÂ C,Â totalÂ N,Â andÂ availableÂ PÂ compared to beforeÂ leaching.Â Amelioration increased theÂ soilÂ CEC,Â even upÂ toÂ theÂ sixthÂ monthÂ leaching,Â the soilÂ CECÂ showedÂ aÂ higher valueÂ thanÂ beforeÂ leaching.Â TheÂ amountÂ ofÂ clayÂ fractionÂ wasÂ relativelyÂ uniformÂ betweenÂ theÂ surfaceÂ andÂ theÂ bottom ofÂ the lysimeter,Â indicating thatÂ Â the adhesiveÂ Â polymerÂ successfullyÂ bondingÂ theÂ clay-sandÂ particlesÂ and prevented clay leaching.